Cláusula penal e o código civil de 2002 - Silva, Leonardo Di Cola N (2008)
The main purpose of this paper is to evidence the need to overrule the unitary theory of the penalty clause, which is the one adopted by the traditional doctrine and according to which the institute has the nature of a liquidated damages clause, regardless of the intent of the parties upon its creation, being any compulsory effect merely secondary. In order to reach such goal, we will initially study the typical functions of the institute in roman law, in the Romano-germanic codes and in common law, and will also discuss the main characteristics and functions that the penalty clause may perform. We will try to demonstrate that the adoption of the unitary theory gives rise to legal problems that are not solvable, and may only be resolved by means of recognizing that there are two different types of penalty clauses, provided that one has an compensatory function and the other has a compulsory function. We will discuss the different rules that apply to each one of them. We have yet two secondary purposes: (i) to discuss the requirements for the equity based judicial review of the penalty clause provided for in article 413 of the Brazilian Civil Code for the cases of manifest excessiveness and partial performance of the obligation, and (ii) to analyze which rights and obligations arising from the penalty clause are transferred as a result of an assignment of credit, debt assumption and assignment of contract. Last, we will differentiate the penalty clause from similar institutes, namely alternative obligation, advance payment ( arras) and astreintes